Injustice for all - Jance, Judith A., 1944- (Avon Suspence ., 1986)
It was like a scene from a movie: the beautiful blond screaming on a Washington beach, a dead man lying at her feet; the dashing Homicide detective arriving to offer kindness and solace to the distressed lady. What it wasn't was a restful vacation for J.P. Beaumont. And now a murderous mix of politics and passion is turning Beau's holiday into a nightmare - and leading the dedicated Seattle cop into the path of a killer whose bloodlust is rapidly becoming an obsession.